PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN KEPULAUAN MERANTI - Ratih Wirda Ningsih; Dedi Afandi; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTThe behavior of the physicians while performing their profession regulated by The Indonesian Code of Medical Ethics or Kode Etik Kedokteran Indonesia (KODEKI). National Health Coverage (NHC) has been implemented since January 2014 which might change the performance of physicians. The aim of this research was to discover implementation of KODEKI values in National Health Coverage Era in Meranti Archipelago Regency that was reflected by the six values of KODEKI. The design of this research was using qualitative approaches with exploration method. Four of general practitioners who serve NHC patients in Meranti Archipelago Regency were selected by using snowball sampling method. Data were collected by doing depth interview recorded with an audio recorder. The result of this research showed that all of informants posses values of altruism, responsibility, idealism, accountability, scientific integrity and social integrity.Keyword : KODEKI values, National Health Coverage